Regeneration of Quercus semecarpifolia Sm. in Shivapuri Hill, Nepal - Shrestha, Bharat B.; Duwadee, Narayan P.; Uprety, Yadav; Shrestha, Uttam B.; Poudel, Srijana (Banko Janakari, 2017)
Abstract on PDF